Community, inequality, and local public goods: evidence from school financing in South Africa - Yamauchi, Futoshi; Nishiyama, Shinichi (International Food Policy Research Institute, 2005)
To examine how local income distribution affects both a community’s ability to pay for schooling and the quality of that schooling, this research merges household and school census data from South Africa. Empirical results are twofold. First, while the median income and the average household income increase school fees, inequality inhousehold income (standard deviation) decreases school fees, which indicates that the lower tail of income distribution pulls down school fees. Second, an increase in school fees significantly improves school quality, decreasing the learner-educator ratio and increasing the number of nonsubsidized educators. The result is consistent with (1) strategic behavior of the low-income group and (2) optimal school fee determination with incomplete interhousehold income transfers. Empirical results and simulations demonstrate the possibility that income and asset inequality may reduce the quality of public goods, decreasing human capital and income growth for the next generation.